Development and evaluation of a self-administered on-line test of memory and attention for middle-aged and older adults - Troyer, Angela K.; Rowe, Gillian; Murphy, Kelly J.; Levine, Brian; Leach, Larry; Hasher, Lynn (Frontiers in Aging Neuroscience, 2014)
There is a need for rapid and reliable Internet-based screening tools for cognitive assessment in middle-aged and older adults. We report the psychometric properties of an on-line tool designed to screen for cognitive deficits that require further investigation. The tool is composed of measures of memory and executive attention processes known to be sensitive to brain changes associated with aging and with cognitive disorders that become more prevalent with age. These measures included spatial working memory, Stroop interference, face-name associative recognition, and number-letter alternation. Normative data were collected from 361 healthy adults age 50 to 79 who scored in the normal range on a standardized measure of general cognitive ability. Participants took the 20-minute on-line test on their home computers, and a subset of 288 participants repeated the test one week later. Analyses of the individual tasks indicated adequate internal consistency, construct validity, test-retest reliability, and alternate version reliability. As expected, scores were correlated with age. The four tasks loaded on the same principle component. Demographically-corrected z-scores from the individual tasks were combined to create an overall score, which showed good reliability and classification consistency. These results indicate the tool may be useful for identifying middle-aged and older adults with lower than expected scores who may benefit from clinical evaluation of their cognition by a health care professional.